STRATEGI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENGUATKAN KINERJA GURU DI SDN KOLURSARI I BANGIL - Rif'atul Khamdiyah; Miftachul Jannah; Munifah Munifah; A. Faizin (STKIP Pesisir Selatan, 2025)
Objective: This study aims to describe and analyze the principal’s academic supervision strategies in strengthening teacher performance at SDN Kolursari I Bangil. The research addresses the phenomenon of how instructional leadership through academic supervision contributes to improving teacher professionalism in primary education. Using a qualitative case study approach, the research explores the real implementation of supervision within the school context. Data were collected through in-depth interviews, participant observation, and document analysis, involving the school principal and six teachers selected through purposive sampling. The data analysis, conducted using Miles and Huberman’s interactive model, revealed four main themes: (1) participatory supervision planning, which engages teachers in determining supervision priorities; (2) humanistic and reflective supervision practices, emphasizing collaborative guidance through classroom observation and peer coaching; (3) appreciative feedback and continuous follow-up, which foster a culture of professional learning; and (4) strengthening teacher performance and professionalism, as reflected in improved pedagogical competence, creativity in teaching, and professional discipline. The findings enrich the theory of instructional leadership by highlighting empathy and collaborative reflection as crucial dimensions of effective academic supervision.